Regulated degradation of HMG CoA reductase requires conformational changes in sterol-sensing domain - Hongwen Chen; Xiaofeng Qi; Rebecca A. Faulkner; Marc M. Schumacher; Linda M. Donnelly; Russell A. DeBose-Boyd; Xiaochun Li (Nature Communications, 2022)
HMG-CoA reductase (HMGCR) is regulated by UBIAD1 and Insigs and initializes cholesterol synthesis. Here authors show that the sterol sensing domain of HMGCR undergoes conformational changes to regulate its degradation via binding its protein modulators.